Unveiling the Enigmatic Origins of Sardinian Toponyms - Brenda Man Qing Ong; Francesco Perono Cacciafoco (Languages, 2022)
With the boom in Indo-European (IE) studies among linguists from the early 20th century, toponymic studies on European place names have been largely based on the Proto-Indo-European (PIE). However, historical and archaeological records of non-IE groups, such as the Nuragic civilization of Sardinia, have presented the possibility of pre-IE/non-IE (Paleo-Sardinian) linguistic stratum influences on certain toponyms in Sardinia, Italy. This article aims to present a meta-study on existing toponymic reconstructions theorized by scholars, while offering a fresh perspective by employing methods of historical phonetic chains and sequences analysis to identify toponyms of interest. Analysis showed that certain Sardinian toponyms contain striking phonetic sequences that are uncharacteristic of PIE, such as *s(a)rd-, *kar-, *-ini, *-ài/*-éi, *#[θ]-. Overall conclusions appear to display the merits of (1) PIE and (2) pre-IE/ non-IE theories. Both provide plausible toponymic reconstructions. (1) The accuracy of IE theories is brought into question, as they appear to rely heavily on phonetic links to existing PIE roots, sometimes with a lack of consideration for other contextual or hydro-geo-morphological factors. (2) Conversely, pre-IE/non-IE theories are found to be highly speculative due to the lack of historical data, and knowledge, about the Paleo-Sardinian language.